Kohesi Leksikal Antonimi dalam Teks Terjemahan Alquran (Surah Makiyyah) - WIDANINGSIH, RETNO, Dra. Atiqa Sabardila, M.Hum (2015)
This study aims to present a variety of shapes, to indentify the type of antonymy lexical cohesion in text translation of the Quran (sura Makiyyah), and to explain the meaning of the translated text of the Quran (sura Makiyyah) that are containing antonymy. This is qualitative research. The design of this research is content analysis. The data in this study are the word and the language that indicate antonymy. Source of data used in this research is the translated text of the Quran (sura Makiyyah). Techniques of collecting data in this research are the see and record methods. This study uses the technique of triangulation theory, namely the study of semantics and discourse. This study uses padan and agih as data analysis techniques. The basic technique used of padan, is referential classify. The advanced techniques is same comparation connectifity. The basic technique used of agih, is the technique for direct element (BUL). The advanced techniques are inserted, replacement, and expand techniques. Based on the analysis, there are three findings. (1) The lexical cohesion (antonymy) contained in the text of the translated text of the Quran (sura Makiyyah) there are some kinds of variations, there are (a) antonymy between word by word (40%), (b) antonymy between words with phrases (4%), (c) antonymy between phrases with phrases (40%), (d) antonymy between clause by clause (39%), (e) antonymy between clause with sentences (1%), (d) antonymy between sentences by sentences (1%). (2) Five types of antonymy in the text of the translation of the Quran (sura Makiyyah), namely antonymy contradiction (59%), place (21%), level (9%), relationship (8%), and mutual responses (3%). (3) The meaning is contained in the translated text (sura Makiyyah) are warnings, commands and prohibitions of Allah to the Prophet Muhammad and his people, as well as residents of Mecca at the time of the Prophet Muhammad. In addition, the stories of the previous prophets and the laws of Islam are also described in the text of the Quran translation (sura Makiyyah).